THE CHAOS INDISTRIBUTED OBJECTS - Ivan Mitrofanovich Pershin; Vladimir Aleksandrovich Utkin (Современная наука и инновации)
We made a research into some peculiarities of responsiveness of the distributed object moving to chaos on the change of the control parameter near the bifurcation line.